Phase I clinical trial of idiotypic DNA vaccine administered as a complex with polyethylenimine to patients with B-cell lymphoma. Issue 6 (3rd June 2017) - Meleshko, A. N.; Petrovskaya, N. A.; Savelyeva, N.; Vashkevich, K. P.; Doronina, S. N.; Sachivko, N. V.
ABSTRACT: We report on the design of a phase I, non-randomized, open-label study of idiotypic DNA vaccination in patients with B-cell non-Hodgkin's lymphoma (ISRCTN31090206). The study uses DNA fusion gene vaccination encoding patient-specific single chain variable fragment, or idiotype, linked to an immunostimulatory sequence. Two types of immunostimulatory sequence are being explored: potato virus X coat protein and human chemokine MIP3α. Linear polyethylenimine with low molecular weight (8 kDa) is used as a synthetic vehicle for vaccine delivery. Humoral and T-cellular immune responses to vaccination will be measured by ELISA and ELISPOT, respectively. The primary study endpoints are safety, tolerability and immunogenicity of DNA-PEI vaccination.